P2.11 Association between genital herpes simpex virus type-2 shedding and presence of bacterial vaginosis-associated bacteria. (8th July 2017) - Johnston, Christine; Magaret, Amalia; Yuhas, Krista; Srinivasan, Sujatha; Proll, Sean; Hughes, James P; Kohler, Christina M; Varon, Dana; Pholsena, Thepthara N; Marrazzo, Jeanne M; Fredricks, David N; Wald, Anna
Abstract : Introduction: Herpes simplex virus type 2 (HSV-2) infection increases the risk of bacterial vaginosis (BV). We hypothesised that the biologic mechanism of this association is that genital HSV-2 shedding increases inflammation, resulting in increased presence and quantity of BV-associated bacteria (BVAB). Methods: HSV-2 seropositive women with a clinical history of BV in the past 12 months collected daily genital swabs for HSV detection and vaginal swabs for Nugent score and analysis of the microbiome for 28 days. BV was defined as Nugent score>=7. Quantitative PCR (qPCR) with species specific primers for Lactobacillus crispatus, L. iners, L. jensenii, Gardnerella vaginalis, Megasphaera and BVAB-2 were performed. HSV was detected using real-time qPCR. The presence of each bacterial species was compared on days with and without HSV shedding using Poisson regression. Results: Forty-eight women (median age 40; 48% white) with a median of 2 genital HSV-2 recurrences in the prior year (range 0–12) were enrolled for a total of 1277 days of observation. Genital HSV shedding was detected on 134 (10%) days. Of 960 days with Nugent score available, BV was present on 351 (37%) days. The risk of BV was not significantly different in the presence of HSV shedding (RR=0.84, 95% CI=0.66–1.07). Several bacterial species appeared to be detected more frequently on days with HSV shedding as compared to days without shedding ( L. crispatus : 53% vs. 44%, L. jensenii : 56% vs. 49%, Megasphaera : 58% vs. 41%, BVAB-2: 49% vs. 37% of days, respectively), although these findings were not statistically significant. The study is 80% completed; data for at least 12 additional women is anticipated, which will provide additional statistical power. Conclusion: Genital HSV-2 shedding may be associated with dynamic shifts in the vaginal microbial community and may increase the presence of BVAB. A study to assess whether the use of suppressive treatment for HSV (daily valacyclovir) decreases the presence of BVAB, or BV (twice weekly metronidazole) decreases HSV shedding, is ongoing.